2001
DOI: 10.1016/s0969-2126(01)00588-3
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Escherichia coli MoeA and Its Relationship to the Multifunctional Protein Gephyrin

Abstract: In eukaryotes, MogA and MoeA are fused into a single polypeptide chain. The corresponding mammalian protein gephyrin has also been implicated in the anchoring of glycinergic receptors to the cytoskeleton at inhibitory synapses. Based on the structures of MoeA and MogA, gephyrin is surmised to be a highly organized molecule containing at least five domains. This multidomain arrangement could provide a structural basis for its functional diversity. The oligomeric states of MoeA and MogA suggest how gephyrin coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 45 publications
6
123
0
Order By: Relevance
“…Biochemical studies have indicated that newly formed MPT remains tightly bound to the MoaD-MoaE complex (MPT synthase) until its transfer to proteins able to bind it with higher affinity (13). MogA and MoeA proteins constitute such candidates and have been shown to bind MPT with distinct affinities (6,11,14). MPT might then be transferred from MPT synthase to MogA by direct protein interaction, and an activated molybdenum species can be subsequently inserted into the MogAbound MPT by the aid of MoeA.…”
mentioning
confidence: 99%
“…Biochemical studies have indicated that newly formed MPT remains tightly bound to the MoaD-MoaE complex (MPT synthase) until its transfer to proteins able to bind it with higher affinity (13). MogA and MoeA proteins constitute such candidates and have been shown to bind MPT with distinct affinities (6,11,14). MPT might then be transferred from MPT synthase to MogA by direct protein interaction, and an activated molybdenum species can be subsequently inserted into the MogAbound MPT by the aid of MoeA.…”
mentioning
confidence: 99%
“…The orientation of domain II was more variable (See Fig. 7, and Supplemental Table III), as was the case for the two wild type structures (19). Domain II variability was most pronounced in the T100A and R137Q variants, where domain II of one monomer of each was poorly defined in the electron density maps.…”
Section: Structural Studies Of Moea Variantsmentioning
confidence: 82%
“…Using the Transformer Site-Directed Mutagenesis Kit (BD/Clontech), site-directed mutagenesis of conserved MoeA residues was performed on pJNeA11, which contains the E. coli moeA gene in a pET11a expression vector (Novagen) (19). Substitutions were made at residues Asp59, Thr100, Arg137, Asp142, Glu188, Asp228, Asp259, Lys275, Lys279, Arg350, and Ser371 using 5′-phosphorylated mutagenic primers overlapping the codon to be modified.…”
Section: Mutagenesis Of Moeamentioning
confidence: 99%
See 2 more Smart Citations